2003
DOI: 10.1063/1.1582362
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of CuInS2-based solar cells by Raman scattering

Abstract: In this work spectroscopic features of the Raman A1 mode of CuInS2 thin films are investigated. A broadening of the A1 mode in combination with an asymmetry towards larger wave numbers is observed. The comparison with parameters of the solar cells formed out of these thin films reveal a direct correlation between the linewidth of the A1 mode and the solar cell data. A significant decrease of open circuit voltage and fill factor of the cells is found for linewidths larger than 3.8 cm−1. For linewidths smaller t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 16 publications
1
31
1
Order By: Relevance
“…[ 14 ] Another peak is also visible at 336 cm −1 which is related to the metastable CuIn 5 S 8 structure. [ 16,17 ] The broadening of the Raman peaks is one characteristic parameter that In Figure 2 , the peak related to the CuIn 5 S 8 phase at 307 cm −1 is pronounced and has a rather comparable intensity to that of the CH structure at 292 cm −1 .…”
Section: Microstructurementioning
confidence: 95%
“…[ 14 ] Another peak is also visible at 336 cm −1 which is related to the metastable CuIn 5 S 8 structure. [ 16,17 ] The broadening of the Raman peaks is one characteristic parameter that In Figure 2 , the peak related to the CuIn 5 S 8 phase at 307 cm −1 is pronounced and has a rather comparable intensity to that of the CH structure at 292 cm −1 .…”
Section: Microstructurementioning
confidence: 95%
“…Through these investigation, it is now also feasible to use laser light scattering or Raman spectroscopy for on-line process control. The latter method also appears to be useful for quality assurance after absorber preparation because certain features of the Raman spectrum of the absorber are found to correlate with the performance of the solar cell [20].…”
Section: Refmentioning
confidence: 98%
“…3 Furthermore, Raman spectroscopy is a contactless method which can be used for quality assessment. 4 Previously it has been found that the presence of CuAu ordering in the CuInS 2 films gives rise to a deterioration of the solar cell performance. 5 The presence of this ordering in the completed CuInS 2 layers, however, is dependent on the starting precursor composition.…”
Section: Introductionmentioning
confidence: 99%